2000
DOI: 10.1074/jbc.m003990200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Transactivation Mediates Substance P-induced Mitogenic Responses in U-373 MG Cells

Abstract: Ligand-induced activation of G protein-coupled receptors is emerging as an important pathway leading to the activation of certain receptors with intrinsic tyrosine kinase activity, such as the epidermal growth factor receptor (EGFR). Substance P (SP) exerts many effects via activation of its G protein-coupled receptor (neurokinin-1, NK-1). SP participates in acute inflammation and activates key proteins involved in mitogenic pathways, such mitogen-activated protein kinases (MAPKs), stimulating DNA synthesis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 53 publications
7
72
0
Order By: Relevance
“…MAPK activation has been previously implicated in mediating GPCR/EGFR signaling pathways in fibroblasts. It is generally believed that MAPK activation mediated through GPCR/EGFR drives cellular proliferation (Sharif et al, 1997;Castagliuolo et al, 2000). However, Santiskulvong et al showed that an EGFRdependent, but MAPK-independent pathway could also mediate the mitogenic effects of GPCR activation (Santiskulvong et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK activation has been previously implicated in mediating GPCR/EGFR signaling pathways in fibroblasts. It is generally believed that MAPK activation mediated through GPCR/EGFR drives cellular proliferation (Sharif et al, 1997;Castagliuolo et al, 2000). However, Santiskulvong et al showed that an EGFRdependent, but MAPK-independent pathway could also mediate the mitogenic effects of GPCR activation (Santiskulvong et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the contribution of GPCR-mediated EGFR transactivation to carcinogenesis and tumor growth (Gschwind et al, 2001). EGFR transactivation by GPCRs has been observed in ovarian cancer cells SK-OV-3 by interleukin-8 (Venkatakrishnan et al, 2000), astroglioma cells U-3T3 MG by substance P (Castagliuolo et al, 2000) and PC-3 prostate cancer cells by bombesin (Prenzel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, prostaglandin E 2 induces the association of a prostaglandin E receptor 4/␤-arrestin 1/c-Src signaling complex, resulting in the transactivation of the EGFR and downstream Akt signaling (41). SP binding to NK-1R causes transactivation of the EGFR and MAPK phosphorylation linked to cell proliferation (9,14) and protection from colitis (15). Several groups also showed an EGFR-Akt-MAPK cross-talk in several cell types (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…NK-1R-deficient mice are protected during the acute phase of colitis, but they have an enhanced inflammatory response at a later stage chronic colitis (15). Improved mucosal healing in the chronic phase of colitis in NK-1R-deficient mice was shown to involve metalloproteinasedependent EGFR transactivation, leading to cell proliferation in colonic fibroblasts and human colonocytes (9,14,15). In this study we report that in colonocytes, SP, by NK-1R activation, stimulates phosphorylation of the antiapoptotic molecule Akt and reduces colonocyte cell death and apoptosis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation